THE PRACTICAL VALUE OF PILGRIMAGE RITUALS BETWEEN THE EASTERN NATIONAL SELF-CONSCIOUSNESS AND SPIRITUALITY IN KAZAKHSTAN (Journal of Oriental Studies, 2019)
This article discusses some documents from the sources of the archive relating to the Hajj in the history of Kazakhstan under the rule of Tsarist Russia. The spiritual value of the Hajj and its role in the creation of religious consciousness in the XIX-XX centuries are discussed. In addition, this article can serve as the beginning for the following research. The article focuses on the analysis of important issues about Hajj.Key words: pilgrimage, Eastern, national consciousness, spirituality, legal madhhabs